Linearized theory of steady high-speed flow - Ward, G. N., author (Cambridge University Press, 2015)
The difficulty of solving the non-linear equations of motion for compressible fluids has caused the linear approximations to these equations to be used extensively in applications to aeronautics. Originally published in 1955, this book is the first permanent work devoted exclusively to the problems involved in this important and rapidly developing subject.